Enhanced Proinflammatory Cytokine Production and Immunometabolic Impairment of NK Cells Exposed to Mycobacterium tuberculosis and Cigarette Smoke - Rao, Yafei; Gai, Xiaoyan; Le, Yanqing; Xiong, Jing; Liu, Yujia; Zhang, Xueyang; Wang, Jundong; Cao, Wenli; Sun, Yongchang (Frontiers in Cellular and Infection Microbiology, 2022)
Aim Smoker COPD patients with chest radiological signs of prior tuberculosis (TB) showed more severe lung damage, but the mechanisms remain unclear. Emerging evidence has implicated NK cells in the pathogenesis of both COPD and TB. The purpose of this study was to delineate the profile and cytokine production of NK-cell subpopulations and their immunometabolic changes after exposure to both cigarette smoke (CS) and Mycobacterium tuberculosis(MTB). Methods We profiled NK-cell subpopulations in terms of percentage and cytokine production by flow cytometry in smoker patients with pulmonary TB (PTB). In an in vitro coexposure model, we investigated proinflammatory cytokine production, glycolytic influx, and oxidative phosphorylation of NK cells under CS extract (CSE) and PPD costimulation. Results Peripheral blood NK cells in smoker patients with active PTB (CS+PTB group) showed altered proportion of subpopulations and excessive proinflammatory cytokine expressions. In vitro, CSE- and PPD-coexposed NK-92 cells displayed enhanced proinflammatory cytokine production, concurrent with decreased glycolytic influx and oxidative phosphorylation. Conclusion Smoker patients with active PTB showed enhanced proinflammatory cytokine expression within altered NK cell subpopulations. CSE and PPD coexposure induced heightened cytokine production concurrent with impaired cell metabolism in NK cells. These novel data suggest a potential role of NK cells in the pathogenesis of lung injury in subjects with coexposure to CS and TB.